Advances in analysis, metabolism and mimicking of human milk lipids. (1st November 2022) - Liu, Qian; Zhao, Junying; Liu, Yan; Qiao, Weicang; Jiang, Tiemin; Liu, Yan; Yu, Xiaowen; Chen, Lijun
Highlights: Qualitative and quantitative LC-MS detection and analysis technologies are reviewed. Concentrations, compositions and distributions of milk lipids differ between mammals. Forms, compositions and structures of lipids affect digestion, absorption and function. Molecular level and entire structure of lipids are important when mimicking human milk lipids. Abstract: Human milk lipids differ from the milk lipids of other mammals in composition and positional distribution of fatty acids. Analysis and detection technology of lipids is key to understanding milk lipids, and thus the concentrations, compositions and distribution characteristics of milk lipids are discussed. Differences between human milk lipids and their substitutes in form, composition and structure affect their digestion, absorption and function in infants. Characteristics and mimicking of human milk lipids have been intensively studied with the objective of narrowing the gap between human milk and infant formulae. Based on the existing achievements, further progress may be made by improving detection techniques, deepening knowledge of metabolic pathways and perfecting fat substitutes. This review detailed the characteristics of human milk lipids and related detection technologies with a view towards providing a clear direction for research on mimicking human milk lipids in formulae to further improve infant nutrition.